Compact ultrawideband filter with reconfigurable band notch characteristics. Issue 2 (3rd April 2023) - Jhariya, Dharmendra Kumar; Mohan, Akhilesh
ABSTRACT: A novel compact ultrawideband (UWB) filter with reconfigurable band notch property is presented. Stepped impedance slotline (SISL) resonator along with two open-ended coupled microstrip is used for the realisation of UWB filter. The WLAN band of rejection is obtained by placing the U-shaped DGS near the SISL resonator. Furthermore, two capacitors are placed in the active slot of U-shaped DGS to obtain WiMAX band of rejection. The proposed UWB filter with reconfigurable band notched characteristics is fabricated and measured. The measured results agree well with the simulated results.